2014
DOI: 10.1016/j.phrp.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Serum Levels of Body Iron Parameters and Insulin Resistance and Metabolic Syndrome in Korean Children

Abstract: ObjectivesAn increase in serum ferritin and levels of the cleaved soluble form of transferrin receptor (sTfR) are related to several metabolic conditions. We evaluated the relationship between body iron status indicators, including ferritin and sTfR, and insulin resistance and metabolic syndrome (MetS) in Korean children.MethodsA cross-sectional study was conducted on 1350 children in Korea. Anthropometrical parameters; lipid profiles; levels of glucose, insulin, and leptin; and iron status indicators, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 29 publications
5
19
0
Order By: Relevance
“…We found the highest level of iron in group of healthy animals receiving SAE, while increased level of iron was found in all groups with MetS compared to healthy rats. Previous study indicates that increased iron stores have been associated with MetS [36]. Changing dietary habits from high-fat to standard food did not result in change of iron, while addition of SAE in this group induced significant rise when compared to MetS group.…”
Section: Discussionmentioning
confidence: 59%
“…We found the highest level of iron in group of healthy animals receiving SAE, while increased level of iron was found in all groups with MetS compared to healthy rats. Previous study indicates that increased iron stores have been associated with MetS [36]. Changing dietary habits from high-fat to standard food did not result in change of iron, while addition of SAE in this group induced significant rise when compared to MetS group.…”
Section: Discussionmentioning
confidence: 59%
“…Several studies have examined sTfR levels in subjects with metabolic syndrome, but their results are quite inconsistent [11, 2830]. In addition, a meta-analysis of prospective studies demonstrated a negative relationship between transferrin saturation and cardiovascular events such as coronary heart disease and acute myocardial infarction [31].…”
Section: Discussionmentioning
confidence: 99%
“…Although some large cross-sectional studies have suggested an association between ferritin levels, and dyslipidemia and some metabolic diseases, few studies have focused on adolescents. Recently, Lee et al reported that children in a group with high HOMA-IR had greater total iron-binding capacity and serum transferrin levels, and were more likely to develop MS, butthey could not demonstrate an association between serum ferritin levels and dyslipidemia parameters [ 40 ]. A study byJeon et al also examined dyslipidemia parameters in Korean adolescents, and observed a link between serum ferritin levels and obesity, but not between serum ferritin levels and MS components [ 24 ].…”
Section: Discussionmentioning
confidence: 99%